Transformation on the Southern Ukrainian Steppe Letters and Papers of Johann Cornies, Volume II: 1836-1842 - Dyck, Harvey L.; Staples, John R. (University of Toronto Press, 2020)
In the eighteenth and nineteenth centuries, the Russian empire opened the grasslands of southern Ukraine to agricultural settlement. Among the immigrants who arrived were communities of Prussian Mennonites, recruited as "model colonists" to bring progressive agricultural methods to the east. The three volumes of Transformation on the Southern Ukrainian Steppe document the Tsarist Mennonite experience through the papers of Johann Cornies (1789-1848), an ambitious and energetic leader of the Mennonite colony of Molochna. This volume covers the years between 1836 and 1842, beginning with the creation of the Mennonite Agricultural Society and ending with the Warkentin Affair, which pushed the Mennonite settlement to the precipice of potential religious and political disaster. Throughout this era, Johann Cornies negotiated a shifting political landscape while guiding his community through equally challenging economic times. Cornies was well connected in the imperial government, and his papers offer a window not just into the world of the Molochna Mennonites, but also into the Tsarist state's relationship with the national minorities of the frontier: Mennonites, Doukhobors, Nogai Tatars, and Jews. This selection of his letters and reports, translated into English, is an invaluable resource for scholars of all aspects of life in Tsarist Ukraine and for those interested in Mennonite history.